Bilateralism in services trade: is there fire behind the (BIT-)smoke? - Rudolf Adlung; Martin Molinuevo (World Trade Organization (WTO), 2008)
Far less attention is given to the even more rapid proliferation of bilateral investment treaties (BITs) and their overlap with obligations assumed by WTO Members under the General Agreement on Trade in Services (GATS). About 60 per cent of world foreign investment stocks are in services and, thus, covered by mode 3 (commercial presence) of the GATS. A closer look reveals that BITs generally apply across a far wider range of sectors, in particular in the case of LDCs and developing countries, than those scheduled under the GATS. Furthermore, a number of obligations enshrined in BITs go beyond their potential counterparts under the GATS. At the same time, since most WTO Members have not listed relevant exemptions from the Most-Favoured-Nation (MFN) clause of the Agreement, their BIT obligations are to be applied on an MFN basis. While this extension may not cause problems in many cases, given generally liberal investment regimes and the focus of most treaties on protecting rather than liberalizing access, inconsistencies remain between the two frameworks. Based on an assessment of relevant provisions, this article discusses options on how WTO Members could proceed.
Keywords: F13; F15; F21; K33; L80; 330; Trade in services; GATS; investment treaties; bilateralism; Internationaler Dienstleistungsverkehr; GATS; Internationales Abkommen; Meistbegünstigung